DETERMINING FACTORS AFFECTING THE LEVEL OF SHARIA ACCOUNTING UNDERSTANDING - Dyah Pravitasari; Aida Hanum Mahmudah (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2022)
The Muslim community in Indonesia uses Islamic law in everyday life, including in social and economic life. Humans fulfill their needs, namely by bartering goods owned by others so that there is no need for recording transactions. Along with the development of the times, humans have difficulty in exchanging goods with other goods because these goods are sometimes not worth the value of the desired goods. This led to less efficient bartering at that time. In the end, humans found a medium of exchange, namely money. Merchants keep records in a simple way. The development of accounting management reached the highest level during the Abbasid Daula. At this time accounting is classified into several specialties such as currency accounting, and book auditing/auditing. Accounting was first recognized in Indonesia around the 1960s and is conventional in nature. Adaptation of accounting developments from Italy. The development of Islamic accounting in Indonesia cannot be separated from the existence of Bank Muamalat Indonesia which was the first Islamic bank in Indonesia in 1991 which officially operated in 1992. It was only in 2002 that an idea and thought emerged on the existence of Islamic accounting, and began to be applied after the existence of standards Islamic banking accounting and the existence of Islamic accounting institutions. Since then, the need for Islamic accounting is needed for the development of society